Iron(II)-catalyzed direct CH cyanoalkylation of 2H-indazoles and coumarins via radical CC bond cleavage. Issue 35 (29th August 2019) - Gao, Pin; Cheng, Yuan-Bo; Yang, Fan; Guo, Li-Na; Duan, Xin-Hua
Graphical abstract: Highlights: Iron-catalyzed radical involved ring-opening of cyclobutanone oxime. C-3 cyanoalkylated 2 H -indazoles and coumarins derivates. Good group tolerance and chemoselectivity toward hetercycles. Abstract: An iron-catalyzed C-3 cyanoalkylation of 2 H -indazole and coumarin derivates with cyclobutanone oxime esters has been accomplished, which proceeds efficiently in a high regioselective manner to construct diverse alkylated 2 H -indazole and coumarin derivates in moderate to good yields. Preliminary mechanistic studies reveal that a distal cyanosubstituted alkyl radicals intermediate would be formed through radical-involved CC bond cleavage of cyclobutanone oximes ester.